1997
DOI: 10.1021/ma9707953
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Induced Structural Changes in Syndiotactic Polystyrene/cis-Decalin Systems

Abstract: Phase transformations in solutions of syndiotactic polystyrene in cis-decalin has been investigated by differential scanning calorimetry, wide and small angle X-ray scattering, and Fourier transformed infrared spectroscopy. The in-situ performed experiments enabled identification of the different modifications without solvent removal. Quenching a solution leads to formation of the helical δ-phase. On heating, this phase transforms into the planar zigzag -phase. The transformation of the helical phase (δ) into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Roels et al have investigated the phase transformation of the sPS/cis-decalin gels by X-ray scattering and Fourier transformed infrared spectroscopy, and found that the gels transform directly into the b form around 140 C without passing through the g form. 20 Rastogi and coworkers have investigated the melting process by X-ray scattering and Raman spectroscopy and it was reported that when heating sPS/benzyl methacrylate gels, the helical d form transformed to g phase firstly then a transition from the helical phase into the planar-zigzag phase (b phase) happened. 21 Thus, in this study, the infrared absorption and XRD spectra of sPS/chloroform gel at various temperatures were performed during the heating process for the identification of the conformational transition.…”
Section: Structure Evolution In Sps/chloroform Gel During Heatingmentioning
confidence: 99%
See 2 more Smart Citations
“…Roels et al have investigated the phase transformation of the sPS/cis-decalin gels by X-ray scattering and Fourier transformed infrared spectroscopy, and found that the gels transform directly into the b form around 140 C without passing through the g form. 20 Rastogi and coworkers have investigated the melting process by X-ray scattering and Raman spectroscopy and it was reported that when heating sPS/benzyl methacrylate gels, the helical d form transformed to g phase firstly then a transition from the helical phase into the planar-zigzag phase (b phase) happened. 21 Thus, in this study, the infrared absorption and XRD spectra of sPS/chloroform gel at various temperatures were performed during the heating process for the identification of the conformational transition.…”
Section: Structure Evolution In Sps/chloroform Gel During Heatingmentioning
confidence: 99%
“…Some research focused on the melting process of sPS/solvent systems. Roels 20 and Rastogi 21 studied the phase transformation of the sPS/cis-decalin system and sPS/benzyl methacrylate gel, respectively, and they found that the gel either transform directly into the b form or transform into the b form through the g form. However, Daniel's previous study on the definition of thermoreversible gels demonstrated that the sPS/ trans-decalin system was not regarded as a gel because the system exhibited a spherulitic morphology and the criteria proposed by Guenet was not fulfilled.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, preliminary in situ X-ray scattering experiments were performed on these systems for a few concentrations. 19 To have a detailed insight into the structural changes during the phase transitions, simultaneous small-and wide-angle X-ray scattering (SAXS and WAXS) and Raman spectroscopy experiments were performed. While SAXS and WAXS can give insight into the morphological changes occurring in the long-and small-range order, the conformational changes occurring during the phase transformations can be followed by Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that syndiotactic polystyrene shows a very complex polymorphism [8][9][10][11][12][13][14][15][16][17][18] as crystallization conditions are varied. a and b, which are characterized by stable planar zigzag conformations, are found in the melt or glassy state of sPS under different thermal-crystallization conditions.…”
Section: Introductionmentioning
confidence: 99%